A few-layer graphene/chlorin e6 hybrid nanomaterial and its application in photodynamic therapy against Candida albicans - Selene Acosta; Carlos Moreno-Aguilar; Dania Hernández-Sánchez; Beatriz Morales-Cruzado; Erick Sarmiento-Gomez; Carla Bittencourt; Luis Octavio Sánchez-Vargas; Mildred Quintana (Beilstein Journal of Nanotechnology, 2020)
The global emergence of multidrug resistance of fungal infections and the decline in the discovery of new antibiotics are increasingly prevalent causes of hospital-acquired infections, among other major challenges in the global health care sector. There is an urgent need to develop noninvasive, nontoxic, and new antinosocomial approaches that work more effectively and faster than current antibiotics. In this work, we report on a biocompatible hybrid nanomaterial composed of few-layer graphene and chlorin e6 (FLG-Ce6) for the photodynamic treatment (PDT) of Candida albicans. We show that the FLG-Ce6 hybrid nanomaterial displays enhanced reactive oxygen species (ROS) generation compared with Ce6. The enhancement is up to 5-fold when irradiated for 15 min at 632 nm with a red light-emitting diode (LED). The viability of C. albicans in the presence of FLG-Ce6 was measured 48 h after photoactivation. An antifungal effect was observed only when the culture/FLG-Ce6 hybrid was exposed to the light source. C. albicans is rendered completely unviable after exposure to ROS generated by the excited FLG-Ce6 hybrid nanomaterial. An increased PDT effect was observed with the FLG-Ce6 hybrid nanomaterial by a significant reduction in the viability of C. albicans, by up to 95%. This is a marked improvement compared to Ce6 without FLG, which reduces the viability of C. albicans to only 10%. The antifungal action of the hybrid nanomaterial can be activated by a synergistic mechanism of energy transfer of the absorbed light from Ce6 to FLG. The novel FLG-Ce6 hybrid nanomaterial in combination with the red LED light irradiation can be used in the development of a wide range of antinosocomial devices and coatings.